Evaluation of La2NiO4 as Anode Material for Solid Oxide Electrolyser Cells. (2nd June 2015) - Egger, Andreas; Schrödl, Nina; Sitte, Werner
Abstract : La2 NiO4 is characterised as potential anode material in solid oxide electrolyser cells (SOECs). Investigations are performed at 800°C and 0.1-0.2 bar oxygen partial pressure over a period of several thousand hours. Trends in chemical surface exchange coefficient and electrical conductivity of a densely sintered sample are identified. In addition, changes in polarisation resistance of a porous anode layer of La2 NiO4 on a button cell under constant anodic current bias of -410 mAcm -2 are recorded. Special emphasis is laid on the impact of Cr-impurities in the surrounding gas phase on the oxygen transport properties and SOEC anode performance. Cr-poisoning is found to depend strongly on the level of humidity in the gas phase as well as on the polarisation conditions.